From sustainable development to circular economy - Magdalena Raftowicz-Filipkiewicz (Economic and Environmental Studies (E&ES), 2016)
This paper is a critical analysis of the sustainable development issue, especially in term of environmental sphere. Author tries to prove that even if well-off countries spend more and more money to protect environment, however the real effects of their actions are relatively week. The current model of economy cannot solve the problem with waste, CO2 emission or extraction of natural resources because it is contrary to the interests of global economic powers. It is therefore proposed to change linear model of economy into circular, which guarantee sustainability and competitiveness simultaneously, what was proven by Spearman's rank correlation coefficient.
Keywords: Q53; Q57; 330; sustainable development; circular economy